A shortening of the life-cycle of major tropical cyclones - Wang,S; Rashid,T; Thorp,H; Toumi,R (Geophysical Research Letters, 2020)
In this study a comprehensive picture of the changing intensity life cycle of major (Category 3 and higher) tropical cyclones (TCs) is presented. Over the past decades, the lifetime maximum intensity has increased, but there has also been a significant decrease in duration of time spent at intensities greater than Category 1. These compensating effects have maintained a stable global meanaccumulated cyclone energy of individual major TCs. The global mean duration of major TCs has shortened by about 1 day from 1982 to 2018. There has been both faster intensification (Categories 1 to 3) and weakening (Categories 3 to 1) by about 40%. The probabilities of rapid intensification and rapid weakening have both risen in the period 2000–2018 compared to 1982–1999. A statistically significant anticorrelation is found between the lifetime maximum intensity and the following duration of the final weakening. This suggests an element of selfregulation of TC life cycles.